PERAMALAN JUMLAH KEDATANGAN WISATAWAN ASING BANDARA DI BALI DAN BANTEN MENGGUNAKAN METODE HOLT-WINTER ADITIF DAN MULTIPLIKATIF - RAIHANAH, RAIHANAH; TRISKA, ANITA; ANGGRIANI, NURSANTI (E-Jurnal Matematika; Vol 12 No 4 (2023), 2023)
Tourism is an important sector in the Indonesian economy. One of the benchmarks for the development of the tourism sector is the number of foreign tourist arrivals to Indonesia. Forecasting the number of foreign tourist arrivals is needed so that actors contributing to the tourism sector can optimize their service efforts. It is necessary to forecast the number of foreign tourist arrivals, especially through the arrival gate at I Gusti Ngurah Rai airport (Bali) and Soekarno-Hatta airport (Banten) as one of the main arrival gates most visited by foreign tourists. This study aims to predict the number of foreign tourist arrivals through the airport by comparing the accuracy of the Holt-Winter's additive and multiplicative method. MAPE (Mean Absolute Percentage Error) and the Durbin Watson statistical test are used and to measure the accuracy of the forecast value against the original data. Overall, the MAPE value and Durbin Watson statistical test result indicate that the additive and multiplicative approaches are good enough to be used. However, judging from the smallest MAPE value, Holt-Winter multiplicative is better used in processing data on the number of foreign tourist arrivals at both I Gusti Ngurah Rai and Soekarno-Hatta airports with MAPE values ??of 7.57% and 6.80% respectively.